Correlation of Predisposing, Enabling and Reinforcing Factors with Dengue Hemorrhagic Fever Prevention in The Work Area of Sikumana Health Center Kupang City - Lubu, Reneldis Arlentin Yuan; Romeo, Petrus; Ndoen, Honey Ivone (Media Kesehatan Masyarakat, 2023)
Dengue Hemorrhagic Fever is an endemic disease caused by the dengue virus and is transmitted through the bite of Aedes aegypti which is often found in tropical and subtropical regions. The lack of preventive behavior is a risk factors affecting DHF incidence. This study aims to determine the correlation of predisposing, enabling and reinforcing factors with dengue hemorrhagic fever prevention. The research was quantitative using an analytical survey method with a cross-sectional design. The population in this study amounted to 51,432 people from six villages in the work area of ​​the Sikumana Health Center, Kupang City. A sampel of 100 people was determined by proportional random sampling. The data analysis used univariate and bivariate analysis. The result showed that 56% of respondents had good knowledge, 50% had negative attitudes, 65% did not receive good information, 55% had poor support from community leaders and 53% did not take dengue prevention measures. Knowledge, attitudes, availability of information and support from community leaders had a significant relationship with dengue prevention measures.